(untitled) (Iranian Journal of Kidney Diseases, 2016)
After 20 years of peritoneal dialysis in Iran, we have encountered with several cases of encapsulating peritoneal sclerosis (EPS) in past few years. Many of these cases remained undiagnosed until advanced stages due to lack of suspicion. In centers with more experience about EPS, mortality has decreased by early diagnostic interventions. Peritoneal dialysis nurses may not be aware of EPS and radiologists are usually not familiar with EPS, either. To increase knowledge about this condition, we decided to present this review article with the case study of one of the 1st patients with EPS at our center. Currently, we have had no data registry of EPS in Iran, yet. Our plan is to develop a national EPS registry in our country which will help to closely monitor these patients.